Analisis UU No. 1 Tahun 1974 Pasal 31 Ayat 3 terhadap Kesetaraan Gender dalam Konteks Perubahan Sosial Kontemporer - Ufi’atun Nur Faizah; Siti Lulun Muthoharoh; Roidatus Shofiyah (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
Article 31 Paragraph 3 of Law Number 1 of 1974 on Marriage, which states that "the husband is the head of the family and the wife is a housewife," raises concerns regarding gender equality and contemporary social dynamics. This provision is considered to reflect a patriarchal legal construction that fails to respond to the evolving gender roles in modern society, where women also actively contribute as breadwinners and decision-makers within the family. This study aims to analyze the relevance of Article 31 Paragraph 3 through a normative, contextual, and inclusive juridical approach. The findings indicate that this provision has the potential to perpetuate gender discrimination and contradicts the principles of justice enshrined in the 1945 Constitution of Indonesia as well as the CEDAW Convention, which has been ratified by Indonesia. Therefore, a reinterpretation of Article 31 Paragraph 3 is necessary to ensure it aligns with contemporary values of equality and current social realities. Reformulating this provision is essential to establish an inclusive and just family law system that keeps pace with societal developments.